A magnesium sand and silicon nitride multiphase microcrystalline glass composite material and preparation method thereof
Through the composite material preparation technology of magnesium sand powder and silicon nitride multi-phase microcrystalline glass powder, the problem of insufficient magnesium spray feed sintering performance and slag corrosion resistance is solved, and efficient magnesium spray feed preparation is achieved, extending the service life of the impregnated tube.
Patent Information
- Application Number
- CN202411936478.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The existing magnesium spray feeding is difficult to form a dense structure during sintering, and the introduced low melt reduces the resistance to slag corrosion and limits the service life of the impregnated tube.
A composite material of magnesium sand powder and silicon nitride multi-phase microcrystalline glass powder is prepared by ball milling, sintering, water quenching, drying and other steps to form a magnesium spray feed with good sintering properties and slag corrosion resistance.
The magnesium spray feeding is achieved to form a dense ceramic bond at high temperature, which significantly improves its sintering performance and slag corrosion resistance, and extends the service life of the impregnated tube.
Smart Images

Figure BDA0005211633240000111 
Figure BDA0005211633240000112
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite refractory materials, and more particularly to a composite material of magnesia and silicon nitride multiphase microcrystalline glass and a preparation method thereof. Background Art
[0002] The converter and RH refining furnace are important equipment in the steel and metallurgical industry. The lining of the converter is made of magnesia-carbon bricks. The RH refining furnace is divided into an immersion tube, a circulation tube, a bottom trough, a middle and upper trough and a hot-bent tube. The lining of the immersion tube is made of magnesia-chrome bricks or magnesia-spinel bricks and a steel structure, and the outer layer is a corundum castable. At present, the life of the immersion tube is a weak point that limits the life of the RH refining furnace.
[0003] During the use of converters and RH immersion tubes, magnesium gunning materials are used for gunning maintenance. However, the current magnesium gunning materials have the following disadvantages: 1) Magnesia sand itself is difficult to sinter; 2) In order to sinter magnesia sand, low-melting materials such as phosphates and borates are introduced into the gunning material scheme, but the introduction of low-melting materials will significantly reduce the gunning material's resistance to slag erosion.
[0004] Therefore, how to develop a magnesium gunning material with excellent performance is an urgent problem to be solved by technicians in this field. Summary of the invention
[0005] In view of this, an object of the present invention is to provide a magnesia and silicon nitride multiphase glass-ceramics composite material and a preparation method thereof to overcome the deficiencies in the prior art.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A composite material of magnesia and silicon nitride multiphase microcrystalline glass, comprising the following raw materials in parts by weight: 60-70 parts of magnesia powder and 30-40 parts of silicon nitride multiphase microcrystalline glass powder;
[0008] Among them, the silicon nitride multiphase microcrystalline glass powder includes the following raw materials in parts by weight: 63-65 parts of silicon nitride powder, 5-20 parts of aluminum oxide powder, 4-6 parts of calcium oxide, 3-5 parts of potassium oxide, 3-5 parts of silicon dioxide powder, 3-5 parts of calcium fluoride, 2-4 parts of sodium oxide and 0.1-5 parts of yttrium oxide.
[0009] Furthermore, the mass fraction of MgO in the above-mentioned magnesia powder is greater than 95%, and the particle size is 0.074 mm;
[0010] The mass fraction of Si3N4 in the silicon nitride micropowder is greater than 99%, and the particle size is 2-3 μm;
[0011] The mass fraction of Al2O3 in the above-mentioned alumina micropowder is greater than 99%, and the particle size is 2-3μm;
[0012] The mass fraction of CaO in the above calcium oxide is greater than 90%, and the particle size is 325 mesh;
[0013] The mass fraction of K2O in the above potassium oxide is greater than 90%, and the particle size is 325 mesh;
[0014] The mass fraction of SiO2 in the above silicon dioxide powder is greater than 95%, and the particle size is 8-12 μm;
[0015] The mass fraction of CaF2 in the above calcium fluoride is greater than 90%, and the particle size is 325 mesh;
[0016] The mass fraction of Na2O in the above sodium oxide is greater than 90%, and the particle size is 325 mesh;
[0017] The mass fraction of Y2O3 in the above yttrium oxide is greater than 99%, and the particle size is 325 meshes.
[0018] A method for preparing a composite material of magnesia and silicon nitride multiphase glass-ceramics, specifically comprising the following steps:
[0019] (1) Weighing the raw materials according to the weight proportions of the above-mentioned magnesia sand and silicon nitride multiphase glass-ceramics composite material;
[0020] (2) mixing silicon nitride powder, aluminum oxide powder, calcium oxide, potassium oxide, silicon dioxide powder, calcium fluoride, sodium oxide and yttrium oxide, and then ball milling, sintering, water quenching, water-milling, drying and sieving to obtain silicon nitride multiphase micro-ceramic glass powder;
[0021] (3) After mixing magnesia powder and silicon nitride multiphase microcrystalline glass powder, the mixture is ball-milled, kneaded at a low speed, a hydrogel solution is added, kneaded at a high speed, pressed into shape, dried, sintered, crushed, and ball-milled again to obtain a magnesia and silicon nitride multiphase microcrystalline glass composite material.
[0022] Furthermore, in the above step (2), the ball milling equipment is an alumina lined ball mill, the rotation speed is 150r / min, and the time is 5-8h; the sintering equipment is a corundum sagger, the temperature is 1400-1450°C, and the insulation time is 2-3h.
[0023] Furthermore, in the above step (2), the drying temperature is 150-200° C., the drying time is 2-3 hours, and the sieve mesh size is 200 meshes.
[0024] Furthermore, in the above step (3), the ball milling equipment is an alumina-lined ball mill, the rotation speed is 150 r / min, and the time is 1 hour.
[0025] Furthermore, in the above step (3), the low-speed mixing device is a planetary high-speed mixer, the rotation speed is 60r / min, and the time is more than 3min; the added mass percentage of the hydrogel solution is 6%; the high-speed mixing device is a planetary high-speed mixer, the rotation speed is 120r / min, and the time is 10-30min.
[0026] Furthermore, in the above step (3), the machine pressing and molding equipment is an electric hydraulic brick press; the drying equipment is a drying kiln, the temperature is 200° C., and the drying time is more than 10 hours.
[0027] Furthermore, in the above step (3), the sintering procedure is: firstly, the temperature is raised to 1300°C at a rate of 10°C / min, kept at this temperature for 3 hours, then the temperature is lowered to 700°C at a rate of 5°C / min, kept at this temperature for 1 hour, and finally cooled to room temperature in the furnace.
[0028] Furthermore, in the above step (3), the particles are crushed to a particle size of less than 5 mm; the ball milling is performed again in an alumina-lined ball mill at a speed of 150 r / min for 1.5 h.
[0029] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:
[0030] 1. The present invention introduces alumina, silicon nitride, silicon dioxide, aluminum fluoride and yttrium oxide into magnesia powder, and prepares a magnesia gunning material that can form a ceramic bond inside at the use temperature (about 900-1200°C) through ordinary sintering at normal pressure, and has good sintering performance and resistance to slag erosion.
[0031] 2. The present invention dopes yttrium oxide into SiO2-CaO-Na2O-K2O-C series glass-ceramics, thereby improving the solubility, sintering performance and bending strength of the glass-ceramics. By using the glass-ceramics as a binder, a dense alumina-based silicon nitride ceramic material can be obtained at medium and low temperatures through liquid phase sintering, making the magnesia sand sintered densely.
[0032] 3. Adding the magnesia powder and yttria-doped-alumina-based silicon nitride multiphase micro-glass-ceramic composite material of the present invention into the magnesium gunning material can form a dense ceramic bond inside the magnesium gunning material, thereby improving the sintering performance and slag erosion resistance of the magnesium gunning material. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] A composite material of magnesia and silicon nitride multiphase microcrystalline glass, comprising the following raw materials by weight: 60 kg of magnesia powder and 40 kg of silicon nitride multiphase microcrystalline glass powder;
[0036] The silicon nitride multiphase microcrystalline glass powder includes the following raw materials by weight: 64.9 kg silicon nitride powder, 20 kg aluminum oxide powder, 4 kg calcium oxide, 3 kg potassium oxide, 3 kg silicon dioxide powder, 3 kg calcium fluoride, 2 kg sodium oxide and 0.1 kg yttrium oxide;
[0037] The mass fraction of MgO in magnesia powder is 95.5% and the particle size is 0.074 mm;
[0038] The mass fraction of Si3N4 in silicon nitride powder is 99.3% and the particle size is 2.5μm;
[0039] The mass fraction of Al2O3 in alumina micropowder is 99.6% and the particle size is 2.5μm;
[0040] The mass fraction of CaO in calcium oxide is 90.4% and the particle size is 325 mesh;
[0041] The mass fraction of K2O in potassium oxide is 90.5%, and the particle size is 325 mesh;
[0042] The mass fraction of SiO2 in silica powder is 95.5% and the particle size is 10μm;
[0043] The mass fraction of CaF2 in calcium fluoride is 91% and the particle size is 325 mesh;
[0044] The mass fraction of Na2O in sodium oxide is 92% and the particle size is 325 mesh;
[0045] The mass fraction of Y2O3 in yttrium oxide is 99.5%, and the particle size is 325 mesh;
[0046] The method for preparing the above-mentioned magnesia and silicon nitride multiphase glass-ceramics composite material specifically comprises the following steps:
[0047] (1) weighing the raw materials according to the weight of the above-mentioned magnesia sand and silicon nitride multiphase glass-ceramic composite material;
[0048] (2) mixing silicon nitride powder, aluminum oxide powder, calcium oxide, potassium oxide, silicon dioxide powder, calcium fluoride, sodium oxide and yttrium oxide, and putting them into an alumina-lined ball mill, and ball milling them at a speed of 150 r / min for 7 h to obtain a mixed powder;
[0049] (3) putting the mixed powder into a corundum sagger, keeping the temperature at 1450°C for 3 hours, and quenching with water to obtain a glass-ceramic frit;
[0050] (4) ball-milling the glass-ceramics frit with water to obtain glass-ceramics;
[0051] (5) drying the glass-ceramics at 200° C. for 3 h, and passing through a 200-mesh sieve to obtain silicon nitride multiphase glass-ceramics powder;
[0052] (6) mixing the magnesia powder and the silicon nitride multiphase microcrystalline glass powder and putting them into an alumina-lined ball mill, and ball milling them at a speed of 150 r / min for 1 h to obtain a mixture;
[0053] (7) The mixture was put into a planetary high-speed mixer, firstly mixed at a low speed of 60 r / min for 3 min, then 6% by weight of the hydrogel solution was added, and then mixed at a high speed of 120 r / min for 30 min to obtain a mixed slurry;
[0054] (8) Pressing the mixed clay material into bricks by an electric hydraulic brick press to obtain a brick blank;
[0055] (9) Pushing the bricks together with the kiln car into a drying kiln and drying them at 200° C. for 10 h to obtain dried bricks;
[0056] (10) The dried bricks were first heated to 1300°C at a rate of 10°C / min, kept at this temperature for 3 hours, then cooled to 700°C at a rate of 5°C / min, kept at this temperature for 1 hour, and finally cooled to room temperature in the furnace to obtain fired bricks;
[0057] (11) The fired bricks were crushed to a particle size of less than 5 mm, and then put into an alumina-lined ball mill and ball-milled at a speed of 150 r / min for 1.5 h to obtain a magnesia and silicon nitride multiphase micro-glass composite material.
[0058] Example 2
[0059] A composite material of magnesia and silicon nitride multiphase microcrystalline glass, comprising the following raw materials by weight: 65 kg of magnesia powder and 35 kg of silicon nitride multiphase microcrystalline glass powder;
[0060] The silicon nitride multiphase microcrystalline glass powder includes the following raw materials by weight: 63kg silicon nitride powder, 15kg aluminum oxide powder, 5kg calcium oxide, 4kg potassium oxide, 4kg silicon dioxide powder, 4kg calcium fluoride, 3kg sodium oxide and 2kg yttrium oxide;
[0061] The mass fraction of MgO in magnesia powder is 95.5% and the particle size is 0.074 mm;
[0062] The mass fraction of Si3N4 in silicon nitride powder is 99.3% and the particle size is 2.5μm;
[0063] The mass fraction of Al2O3 in alumina micropowder is 99.6% and the particle size is 2.5μm;
[0064] The mass fraction of CaO in calcium oxide is 90.4% and the particle size is 325 mesh;
[0065] The mass fraction of K2O in potassium oxide is 90.5%, and the particle size is 325 mesh;
[0066] The mass fraction of SiO2 in silica powder is 95.5% and the particle size is 10μm;
[0067] The mass fraction of CaF2 in calcium fluoride is 91% and the particle size is 325 mesh;
[0068] The mass fraction of Na2O in sodium oxide is 92% and the particle size is 325 mesh;
[0069] The mass fraction of Y2O3 in yttrium oxide is 99.5%, and the particle size is 325 mesh;
[0070] The method for preparing the above-mentioned magnesia and silicon nitride multiphase glass-ceramics composite material specifically comprises the following steps:
[0071] (1) weighing the raw materials according to the weight of the above-mentioned magnesia sand and silicon nitride multiphase glass-ceramic composite material;
[0072] (2) mixing silicon nitride powder, aluminum oxide powder, calcium oxide, potassium oxide, silicon dioxide powder, calcium fluoride, sodium oxide and yttrium oxide, and putting them into an alumina-lined ball mill, and ball milling them at a speed of 150 r / min for 6 hours to obtain a mixed powder;
[0073] (3) putting the mixed powder into a corundum sagger, keeping the temperature at 1400°C for 2.5 hours, and quenching with water to obtain a glass-ceramic frit;
[0074] (4) ball-milling the glass-ceramics frit with water to obtain glass-ceramics;
[0075] (5) drying the glass-ceramics at 150° C. for 2 h, and passing through a 200-mesh sieve to obtain silicon nitride multiphase glass-ceramics powder;
[0076] (6) mixing the magnesia powder and the silicon nitride multiphase microcrystalline glass powder and putting them into an alumina-lined ball mill, and ball milling them at a speed of 150 r / min for 1 h to obtain a mixture;
[0077] (7) The mixture was put into a planetary high-speed mixer, firstly mixed at a low speed of 60 r / min for 3 min, then 6% by weight of the hydrogel solution was added, and then mixed at a high speed of 120 r / min for 15 min to obtain a mixed slurry;
[0078] (8) Pressing the mixed clay material into bricks by an electric hydraulic brick press to obtain a brick blank;
[0079] (9) Pushing the bricks together with the kiln car into a drying kiln and drying them at 200° C. for 10 h to obtain dried bricks;
[0080] (10) The dried bricks were first heated to 1300°C at a rate of 10°C / min, kept at this temperature for 3 hours, then cooled to 700°C at a rate of 5°C / min, kept at this temperature for 1 hour, and finally cooled to room temperature in the furnace to obtain fired bricks;
[0081] (11) The fired bricks were crushed to a particle size of less than 5 mm, and then put into an alumina-lined ball mill and ball-milled at a speed of 150 r / min for 1.5 h to obtain a magnesia and silicon nitride multiphase micro-glass composite material.
[0082] Example 3
[0083] A composite material of magnesia and silicon nitride multiphase microcrystalline glass, comprising the following raw materials by weight: 65 kg of magnesia powder and 35 kg of silicon nitride multiphase microcrystalline glass powder;
[0084] The silicon nitride multiphase microcrystalline glass powder includes the following raw materials by weight: 65 kg silicon nitride powder, 10 kg aluminum oxide powder, 5 kg calcium oxide, 4 kg potassium oxide, 5 kg silicon dioxide powder, 4 kg calcium fluoride, 3 kg sodium oxide and 4 kg yttrium oxide;
[0085] The mass fraction of MgO in magnesia powder is 95.5% and the particle size is 0.074 mm;
[0086] The mass fraction of Si3N4 in silicon nitride powder is 99.3% and the particle size is 2.5μm;
[0087] The mass fraction of Al2O3 in alumina micropowder is 99.5% and the particle size is 2.5μm;
[0088] The mass fraction of CaO in calcium oxide is 90.4% and the particle size is 325 mesh;
[0089] The mass fraction of K2O in potassium oxide is 90.5%, and the particle size is 325 mesh;
[0090] The mass fraction of SiO2 in silica powder is 95.5% and the particle size is 10μm;
[0091] The mass fraction of CaF2 in calcium fluoride is 91% and the particle size is 325 mesh;
[0092] The mass fraction of Na2O in sodium oxide is 92% and the particle size is 325 mesh;
[0093] The mass fraction of Y2O3 in yttrium oxide is 99.5%, and the particle size is 325 mesh;
[0094] The method for preparing the above-mentioned magnesia and silicon nitride multiphase glass-ceramics composite material specifically comprises the following steps:
[0095] (1) weighing the raw materials according to the weight of the above-mentioned magnesia sand and silicon nitride multiphase glass-ceramic composite material;
[0096] (2) mixing silicon nitride powder, aluminum oxide powder, calcium oxide, potassium oxide, silicon dioxide powder, calcium fluoride, sodium oxide and yttrium oxide, and putting them into an alumina-lined ball mill, and ball milling them at a speed of 150 r / min for 5 h to obtain a mixed powder;
[0097] (3) putting the mixed powder into a corundum sagger, keeping the temperature at 1420° C. for 2.5 h, and quenching with water to obtain a glass-ceramic frit;
[0098] (4) ball-milling the glass-ceramics frit with water to obtain glass-ceramics;
[0099] (5) drying the glass-ceramics at 180° C. for 2.5 h, and passing through a 200-mesh sieve to obtain silicon nitride multiphase glass-ceramics powder;
[0100] (6) mixing the magnesia powder and the silicon nitride multiphase microcrystalline glass powder and putting them into an alumina-lined ball mill, and ball milling them at a speed of 150 r / min for 1 h to obtain a mixture;
[0101] (7) The mixture was put into a planetary high-speed mixer, firstly mixed at a low speed of 60 r / min for 3 min, then 6% by weight of the hydrogel solution was added, and then mixed at a high speed of 120 r / min for 10 min to obtain a mixed slurry;
[0102] (8) Pressing the mixed clay material into bricks by an electric hydraulic brick press to obtain a brick blank;
[0103] (9) Pushing the bricks together with the kiln car into a drying kiln and drying them at 200° C. for 10 h to obtain dried bricks;
[0104] (10) The dried bricks were first heated to 1300°C at a rate of 10°C / min, kept at this temperature for 3 hours, then cooled to 700°C at a rate of 5°C / min, kept at this temperature for 1 hour, and finally cooled to room temperature in the furnace to obtain fired bricks;
[0105] (11) The fired bricks were crushed to a particle size of less than 5 mm, and then put into an alumina-lined ball mill and ball-milled at a speed of 150 r / min for 1.5 h to obtain a magnesia and silicon nitride multiphase micro-glass composite material.
[0106] Example 4
[0107] A composite material of magnesia and silicon nitride multiphase microcrystalline glass, comprising the following raw materials by weight: 70 kg of magnesia powder and 30 kg of silicon nitride multiphase microcrystalline glass powder;
[0108] The silicon nitride multiphase microcrystalline glass powder includes the following raw materials by weight: 65 kg silicon nitride powder, 5 kg aluminum oxide powder, 6 kg calcium oxide, 5 kg potassium oxide, 5 kg silicon dioxide powder, 5 kg calcium fluoride, 4 kg sodium oxide and 5 kg yttrium oxide;
[0109] The mass fraction of MgO in magnesia powder is 95.5% and the particle size is 0.074 mm;
[0110] The mass fraction of Si3N4 in silicon nitride powder is 99.3% and the particle size is 2.5μm;
[0111] The mass fraction of Al2O3 in alumina micropowder is 99.6% and the particle size is 2.5μm;
[0112] The mass fraction of CaO in calcium oxide is 90.4% and the particle size is 325 mesh;
[0113] The mass fraction of K2O in potassium oxide is 90.5%, and the particle size is 325 mesh;
[0114] The mass fraction of SiO2 in silica powder is 95.5% and the particle size is 10μm;
[0115] The mass fraction of CaF2 in calcium fluoride is 91% and the particle size is 325 mesh;
[0116] The mass fraction of Na2O in sodium oxide is 92% and the particle size is 325 mesh;
[0117] The mass fraction of Y2O3 in yttrium oxide is 99.5%, and the particle size is 325 mesh;
[0118] The method for preparing the above-mentioned magnesia and silicon nitride multiphase glass-ceramics composite material specifically comprises the following steps:
[0119] (1) weighing the raw materials according to the weight of the above-mentioned magnesia sand and silicon nitride multiphase glass-ceramic composite material;
[0120] (2) mixing silicon nitride powder, aluminum oxide powder, calcium oxide, potassium oxide, silicon dioxide powder, calcium fluoride, sodium oxide and yttrium oxide, and putting them into an alumina-lined ball mill, and ball milling them at a speed of 150 r / min for 6 hours to obtain a mixed powder;
[0121] (3) putting the mixed powder into a corundum sagger, keeping the temperature at 1450°C for 2.5 hours, and quenching with water to obtain a glass-ceramic frit;
[0122] (4) ball-milling the glass-ceramics frit with water to obtain glass-ceramics;
[0123] (5) drying the glass-ceramics at 200° C. for 3 h, and passing through a 200-mesh sieve to obtain silicon nitride multiphase glass-ceramics powder;
[0124] (6) mixing the magnesia powder and the silicon nitride multiphase microcrystalline glass powder and putting them into an alumina-lined ball mill, and ball milling them at a speed of 150 r / min for 1 h to obtain a mixture;
[0125] (7) The mixture was put into a planetary high-speed mixer, firstly mixed at a low speed of 60 r / min for 3 min, then 6% by weight of the hydrogel solution was added, and then mixed at a high speed of 120 r / min for 25 min to obtain a mixed slurry;
[0126] (8) Pressing the mixed clay material into bricks by an electric hydraulic brick press to obtain a brick blank;
[0127] (9) Pushing the bricks together with the kiln car into a drying kiln and drying them at 200° C. for 10 h to obtain dried bricks;
[0128] (10) The dried bricks were first heated to 1300°C at a rate of 10°C / min, kept at this temperature for 3 hours, then cooled to 700°C at a rate of 5°C / min, kept at this temperature for 1 hour, and finally cooled to room temperature in the furnace to obtain fired bricks;
[0129] (11) The fired bricks were crushed to a particle size of less than 5 mm, and then put into an alumina-lined ball mill and ball-milled at a speed of 150 r / min for 1.5 h to obtain a magnesia and silicon nitride multiphase micro-glass composite material.
[0130] Performance Testing
[0131] 1. Performance test
[0132] The magnesia sand and silicon nitride multiphase micro-glass composite materials prepared in Examples 1-4 were respectively tested for their flexural strength (Mpa) in a hot state at 1600°C*30min according to GB / T3002-2004, and their erosion index (%) in a static crucible method slag resistance test at 1600°C was tested according to GB / T8931-2007.
[0133] The results are shown in Table 1.
[0134] Table 1 Performance test of magnesia and silicon nitride multiphase glass-ceramic composite materials of Examples 1-4
[0135]
[0136] It can be seen from Table 1 that the magnesia and silicon nitride multiphase glass-ceramics composite materials of Examples 1-4 all have excellent flexural strength and resistance to slag erosion.
[0137] 2. Practical Application
[0138] The magnesia sand and silicon nitride multiphase micro-glass-ceramic composite material prepared in Example 4 was taken, and a commercially available magnesia gunning material was used as a comparison, and was actually applied in a 200-ton RH refining furnace immersion tube and a 200-ton converter of a branch of Anshan Iron and Steel Co., Ltd., and the number of furnaces used was counted.
[0139] The results are shown in Table 2.
[0140] Table 2 Use of heats of magnesia and silicon nitride multiphase glass-ceramic composite materials in Example 4
[0141]
[0142] It can be seen from Table 2 that, compared with a certain commercially available magnesium gunning material, the use number of furnaces of the magnesium sand and silicon nitride multiphase micro-ceramic glass composite material in Example 4 is significantly increased.
[0143] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A composite material of magnesium sand and silicon nitride multiphase glass-ceramics, characterized in that: The method comprises the following raw materials in parts by weight: 60-70 parts of magnesia powder and 30-40 parts of silicon nitride multiphase microcrystalline glass powder; The silicon nitride multiphase microcrystalline glass powder comprises the following raw materials in parts by weight: 63-65 parts of silicon nitride powder, 5-20 parts of aluminum oxide powder, 4-6 parts of calcium oxide, 3-5 parts of potassium oxide, 3-5 parts of silicon dioxide powder, 3-5 parts of calcium fluoride, 2-4 parts of sodium oxide and 0.1-5 parts of yttrium oxide.
2. The multiphase glass-ceramic composite material of magnesia and silicon nitride according to claim 1, characterized in that: The mass fraction of MgO in the magnesia powder is greater than 95%, and the particle size is 0.074 mm; The mass fraction of Si3N4 in the silicon nitride micropowder is greater than 99%, and the particle size is 2-3 μm; The mass fraction of Al2O3 in the alumina micropowder is greater than 99%, and the particle size is 2-3 μm; The mass fraction of CaO in the calcium oxide is greater than 90%, and the particle size is 325 mesh; The mass fraction of K2O in the potassium oxide is greater than 90%, and the particle size is 325 mesh; The mass fraction of SiO2 in the silicon dioxide micropowder is greater than 95%, and the particle size is 8-12 μm; The mass fraction of CaF2 in the calcium fluoride is greater than 90%, and the particle size is 325 mesh; The mass fraction of Na2O in the sodium oxide is greater than 90%, and the particle size is 325 mesh; The mass fraction of Y2O3 in the yttrium oxide is greater than 99%, and the particle size is 325 meshes.
3. A method for preparing a composite material of magnesia sand and silicon nitride multiphase glass-ceramics, characterized in that: The specific steps include: (1) Weighing the raw materials according to the weight proportions of the magnesia sand and silicon nitride multiphase glass-ceramics composite material according to claim 1 or 2; (2) mixing silicon nitride powder, aluminum oxide powder, calcium oxide, potassium oxide, silicon dioxide powder, calcium fluoride, sodium oxide and yttrium oxide, and then ball milling, sintering, water quenching, water-milling, drying and sieving to obtain silicon nitride multiphase micro-ceramic glass powder; (3) After mixing the magnesia powder and the silicon nitride multiphase microcrystalline glass powder, the mixture is ball-milled, kneaded at a low speed, a hydrogel solution is added, kneaded at a high speed, pressed into shape, dried, sintered, crushed, and ball-milled again to obtain the magnesia and silicon nitride multiphase microcrystalline glass composite material.
4. The method for preparing a composite material of magnesia and silicon nitride multiphase glass-ceramics according to claim 3, characterized in that: In step (2), the ball milling equipment is an alumina lined ball mill, the rotation speed is 150r / min, and the holding time is 5-8h; the sintering equipment is a corundum sagger, the temperature is 1400-1450°C, and the holding time is 2-3h.
5. The method for preparing a composite material of magnesia and silicon nitride multiphase glass-ceramics according to claim 3, characterized in that: In step (2), the drying temperature is 150-200° C. and the drying time is 2-3 hours; and the sieving mesh size is 200 meshes.
6. The method for preparing a composite material of magnesia and silicon nitride multiphase glass-ceramics according to claim 3, characterized in that: In step (3), the ball milling equipment is an alumina lined ball mill, the rotation speed is 150r / min, and the time is 1h.
7. The method for preparing a composite material of magnesia and silicon nitride multiphase glass-ceramics according to claim 3, characterized in that: In step (3), the low-speed mixing device is a planetary high-speed mixer, the rotation speed is 60r / min, and the time is more than 3min; the added mass percentage of the hydrogel solution is 6%; the high-speed mixing device is a planetary high-speed mixer, the rotation speed is 120r / min, and the time is 10-30min.
8. The method for preparing a composite material of magnesia and silicon nitride multiphase glass-ceramics according to claim 3, characterized in that: In step (3), the machine pressing and molding equipment is an electric hydraulic brick press; the drying equipment is a drying kiln, the temperature is 200° C., and the time is more than 10 hours.
9. The method for preparing a multiphase glass-ceramic composite material of magnesia and silicon nitride according to claim 3, characterized in that: In step (3), the sintering procedure is: firstly, heating to 1300°C at a rate of 10°C / min, keeping the temperature for 3h, then cooling to 700°C at a rate of 5°C / min, keeping the temperature for 1h, and finally cooling to room temperature in the furnace.
10. The method for preparing a multiphase glass-ceramic composite material of magnesia and silicon nitride according to claim 3, characterized in that: In step (3), the crushing to a particle size of less than 5 mm; the re-ball milling equipment is an alumina-lined ball mill with a rotation speed of 150 r / min and a time of 1.5 h.
Citation Information
Cited By
High-damping ceramic-based machine tool moving part and preparation method thereof
CN122233768A